Mortality predictors of pneumonia in children - Priyanti Kisworini; Amalia Setyati; Sutaryo Sutaryo (Paediatrica Indonesiana, 2010)
Background Pneumonia is one of the main causes of death in children in developing countries. It is important to identify clinical signs, demographic factors, and laboratory data which can be used to predict children who have higher risk of mortality from pneumonia.Objective To find the clinical signs, demographic factors and laboratory data that can be used as predictors of mortality from pneumonia.Methods T his historical case􀀽control study was carried out in Sardjito Hospital between January 2004 and December 2006. Data were obtained from medical records. Differential proportion between groups was analyzed with chi square. Regression analysis was used to identify clinical factors, demographic factors and laboratory factors that associated with mortality from pneumonia.Results Fifty􀀽eight patients were enrolled in this study, 29 patients were dead (case group) and 29 patients were cured (control group). Baseline data between the two groups were similar in terms of gender and mean of age. Bivariate analyses show that the predictors of mortality in children with pneumonia were: age < 1 year (OR3.11, 95% CI 1.06 to 9.08), malnutrition (OR 7.30,95% CI 1.62- to 21.03), age of the mother < 20 years (OR 2.21,95%CI 1.64 to 2.97),t achycardia (OR 6.075,95% CI 1.18 to 31.24), and anemia (OR 5 .83, 95% CI 1.88 to 18.10). Logistic regression analysis shows that tachycardia (OR 6.04, 95% CI 1.01 to 36.17) and anemia (OR 4.41,95% CI 1.25 to 15.51) were predictor of mortality in children 'With pneumonia.Conclusions Tachycardia and anemia play as independent mortality predictors of pneumonia in children.